Two kinds of naturalism in ethics - Sinclair, Neil (Springer, 2006)
What are the conditions on a successful naturalistic account of moral properties? In this paper I discuss one such condition: the possibility of moral concepts playing a role in good empirical theories on a par with those of the natural and social sciences. I argue that Peter Railton’s influential account of moral rightness fails to meet this condition, and thus is only viable in the hands of a naturalist who doesn’t insist on it. This conclusion generalises to all versions of naturalism that give a significant role to a dispositional characterisation of moral properties. I also argue, however, that the epistemological and semantic motivations behind naturalism are consistent with a version of naturalism that abandons the condition.